Mukherjee, Souvik. 2022. Videogames in the Indian Subcontinent. Development, Culture(s) and Representations. Bloomsbury - Zeiler, Xenia (CyberOrient, 2023)
The book Videogames in the Indian Subcontinent. Development, Culture(s) and Representations is the first ever comprehensive presentation and discussion of material spanning over all nations of South Asia, including Bangladesh, Bhutan, India, the Maldives, Nepal, Pakistan, and Sri Lanka. Discussed by the leading expert on the theme, it offers both an overview of as well as numerous detailed examples of both, historical and contemporary developments. Appropriately, this work also situates the regional characteristics in larger global contexts and cultural flows, and contemporary developments in historical contexts.